Production and characterization of monoclonal antibodies to the edta extract of Leptospira interrogans, serovar icterohaemorrhagiae - Leite,Lilian Terezinha de Queiroz (1996)
Monoclonal antibodies (MABs) ivere produced against an etbylenediaminetetraacetate (EDTA) extract of Leptospira interrogans serovar icterohaemorrhagiae being characterized by gel precipitation as IgM and IgG (IgGl and IgG2b). The EDTA extract was detected as several bands by silver staining in SDS-PAGE. In the Western blot the bands around 20 KDa reacted with a monoclonal antibody, 47B4D6, and was oxidized by periodate and was not digested by pronase, suggesting that the determinant is of carbohydrate nature, lmmunocytochemistry, using colloidal gold labeling, showed that an EDTA extract determinant recognized by monoclonal antibody 47B4D6, is localized under the outer envelope of serovar icterohaemorrhagiae. Hoe AIAB raised against the EDTA extract was not able to protect hamsters from lethal challenge with virulent homologous leptospires.